Quality of life and clinical and demographic characteristics of patients with cutaneous squamous cell carcinoma submitted to tumor resection by double-bladed scalpel - Daniel Ongaratto Barazzetti; Pedro Henrique Ongaratto Barazzetti; Bárbara Thomé Cavalheiro; Jorge Bins Ely; Daniel Holthausen Nunes; Ana Maria Nunes de Faria Stamm
Abstract: Background: Non-melanoma skin cancer accounts for a third of all malignancies registered in Brazil, with squamous cell carcinoma (SCC) being one of its subtypes. It develops in photo-exposed areas, affecting social habits and causing negative influence on quality of life (QoL). Objectives: To evaluate QoL in patients with primary cutaneous SCC. Methods: A cross-sectional study was performed in patients with clinical diagnosis of SCC, corroborated by dermoscopy and confirmed by histopathology; prior to resection of the tumor using the double-blade scalpel technique, a questionnaire on the Dermatology Life Quality Index (DLQI) was applied. Results: Among the 46 evaluated patients, mean age was 67.1 ± 16.0 years, with a predominance of males, low educational level and socioeconomic status, Fitzpatrick II phototype, history of outdoor work, and tumor location in exposed photo areas. Mean DLQI was 4.02 ± 0.63, and in the categorization, 11 (23.9%) had a moderate to severe negative effect on QoL. The skin tumor had a negative impact on daily activities (33% of cases), treatment effects (30%), and symptoms and feelings (29%). Study limitations: There is no gold standard instrument for assessing QoL in dermatological patients. Conclusion: In the study sample, one-fourth of patients with SCC had a moderate to severe negative effect on quality of life.